The Hillshire Farm brand : growth opportunities in snacking - Roese, Neal J.; Pavlus, John (London : Kellogg School of Management, 2020)
Megan Huddleston, head of marketing for Tyson's Hillshire Farm brand is seeking new growth with a brand extension. But which product line and brand envelope would most effectively leverage Americans' shifting eating habits? This case allows students to explore the key tradeoffs in brand extension with the overarching goals of gaining revenue growth while protecting brand equity.
Orginally Published InRoese, N. J., & Pavlus, J. (2020). The Hillshire Farm Brand: Growth Opportunities in Snacking. 5-420-751. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hillshire Farm -- Case studies; Branding (Marketing) -- Case studies